EFFECTIVITNESS OF SETS MODEL WITH LOCAL WISDOM ON CREATIVE THINKING SKILLS IN BIOLOGY LEARNING - Rikizaputra, Rikizaputra; Firda, Arlian; Sembiring, Alkhudri; Ramadansur, Rahmat; Pikri, Pikri (Bio-Lectura : Jurnal Pendidikan Biologi, 2025)
The 21st century demands that learning in schools must be able to encourage students to develop their critical and creative thinking skills in order to be able to compete in the global world. But on the other hand, it is also expected that students do not forget their national identity. So that biology material in schools that is very closely related to the surrounding environment needs to be linked to existing local wisdom. Therefore, an appropriate learning strategy is needed to accommodate all these interests. This study aims to determine the effectiveness of the SETS (Science Environment Technology Society) model containing local wisdom on creative thinking skills in environmental material. Using quasi-experimental research with a nonequivalent pretest-posttest control group design. The population is all students of class X SMAN 7 Pekanbaru with a sample of two classes taken randomly. Data were collected through tests with multiple-choice test instruments. Data analysis with parametric t-test statistics. The results of the study showed that the average N-Gain of the control class was 0.46 (moderate) and the experimental class was 0.51 (moderate). The results of the N-Gain t-test obtained a sig value. (2-tailed) 0.000<0.05 then reject Ho. This means that the application of SETS learning containing local wisdom is effective in increasing students' creative thinking skills. ABSTRAK Abad 21 menuntut pembelajaran disekolah harus mampu mendorong siswa untuk mengembangkan keterampilan berpikir kritis dan kreatifnya agar mampu bersaing di dunia global. Tapi disisi lain juga diharapkan agar siswa tidak melupakan jati diri bangsanya. Sehingga materi biologi di sekolah yang sangat erat kaitannya dengan lingkungan sekitar perlu dikaitkan dengan kearifan lokal yang ada. Oleh karena itu perlu strategi pembelajaran yang tepat untuk mengakomodir semua kepentingan tersebut. Penelitian ini bertujuan untuk mengetahui efektifitas model SETS (Science Environment Tecnology Society) bermuatan kearifan lokal terhadap keterampilan berpikir kreatif pada materi lingkungan. Menggunakan penelitian quasi eksperimen dengan desain Snonequivalen pretes-posttest control group. Populasi semua siswa kelas X SMAN 7 Pekanbaru dengan sampel dua kelas yang diambil csecara random. Data dikumpulkan melalui tes dengan instrument soal tes pilihan ganda. Analsis data dengan statistic parametric uji t. Hasil penelitian menunjukkan rerata N-Gain kelas kontrol sebesar 0,46 (sedang) dan kelas eksperimen sebesar 0,51 (sedang). Hasil uji-t N-Gain diperoleh nilai sig. (2-tailed) 0,000<0,05 maka tolak Ho. Artinya penerapan pembelajaran SETS bermuatan kearifan lokal efektif meningkatkan keterampilan berpikir kreatif siswa.